If not us, then who? Ethnographic insights into nurses’ role in redesigning a rural health service to meet changing demands - Helle Krone-Hjertstrøm; Bente Norbye; Birgit Abelsen; Aud Uhlen Obstfelder (BMC Health Services Research)
Abstract Background The increasing prevalence of chronic diseases and an ageing population challenge healthcare delivery, particularly in rural areas. Redesigning health services to meet these changing demands is crucial, esially in rural healthcare where service providers face capacity and expertise limitations. This paper explores how the rural context influences nurses' roles in the clinic and the process of redesigning a rural emergency clinic in Northern Norway to include a Municipal Inpatient Acute Care Service (MipAC). Methods The study combines observations (250 h), several in situ interviews with healthcare personnel, and individual in-depth interviews with nurses (n = 8) at the emergency clinic in a rural area in northern Norway. To explore nurses’ role in the clinic and in the redesign process, we were inspired by the theory of social organisation of healthcare work. Results The study highlights three prominent aspects of the rural dimension that are crucial for understanding the nurses’ role in the redesign process. First, ‘Absent present PCPs’ highlights how nurses ensure continuity of care during the intermittent absence of primary care physicians (PCPs). Second, ‘Learning without doing’ shows how the nurses utilized their competence, past experiences, and understanding of local conditions to adapt standardised guidelines, develop new work processes, and establish a framework that compensates for the lack of practical experience, enabling the clinic to function effecively under potential challanging circumstances. Third, ‘The local nurse' emphasises how the nurses’ connection to the local community influences how they organize care; they are commited to local adaptation and ensuring that "their" residents have acess to what they consider high-quality services. Conclusion The nurses’, experience, dedication, and orientation towards the local community were crucial for the redesign process. The nurses ensured the continuiety in the clinic, despite the PCP's sporadic presence, adapted the standardized guidelines to a rural context and were crucial in organising patient care in the rural area. The study shows that the nurses organizing work, which often remains invisible, is essential in the redesign process. The study indicates that the scope of practice for nurses is more extensive in rural areas and should receive greater attention. in both research, practice and health policy